CREATIVITY AND INNOVATION COLLABORATION IN THEMATIC LEARNING: A REVIEW OF THE LITERATURE - Rengga Yudha Santoso; Ali Mansur; Muhammad Akbar Hajuan (Adisam Publisher, 2025)
The purpose of this study is to investigate Creativity and Innovation Collaboration in Thematic Learning: A Review of the Literature. The form of this research is descriptive, analytical, and critical. Therefore, the author can provide a comprehensive description of the investigation, Creativity and Innovation Collaboration in Thematic Learning: A Review of the Literature. In this study, the author optimally uses two data sources related to this research, namely. Primary data sources and secondary data sources. The study's results demonstrate that synergy and collaboration between creativity and innovation in thematic learning have a positive impact on both student learning outcomes and creativity. The application of creative and innovative approaches can create a more meaningful and enjoyable learning experience, thereby increasing student motivation and involvement in the learning process.